Systematic Literature Review Riset Pelaporan Keuangan BLUD - Y Anni Aryani; Sutaryo Sutaryo; Taufiq Arifin; Doddy Setiawan; Evi Gantyowati; Payamta Payamta; Isna Putri Rahmawati; Nurrahmawati; Dian Perwitasari (Journal Of Business, Finance, and Economics (JBFE), 2024)
This research seeks to examine the extent to which research related to BLUD financial reporting has been carried out by researchers in Indonesia since the publication of Permendagri Number 79 of 2018. By using a systematic literature review on the SINTA portal, researchers found that research related to BLUD financial reporting is still very limited. The existing research in the literature to date still contains more descriptive research and case study research compared to causality research with empirical studies. Previous research also had limited research objects, only covering one BLUD with case studies or just one Regency/City for empirical research. The analysis carried out is still relatively simple and not yet comprehensive. Referring to the results of a systematic literature review, this research emphasizes the urgency of strengthening research related to BLUD financial reporting. Future research can increase the scope of observations followed by more in-depth analysis to produce more comprehensive research findings so as to produce constructive recommendations for BLUD financial reporting. With more comprehensive research, future researchers can improve the quality of publications by publishing more articles in SINTA 2 indexed journals or even reputable international journals. Thus, the contribution of research related to BLUD in the public sector accounting literature in Indonesia can increase and become increasingly significant.